PENGARUH LINGKUNGAN KERJA, KETERLIBATAN KERJA TERHADAP KOMITMEN PEKERJAAN PADA KARYAWAN CAFÉBLUE DOORS DI SURABAYA - Teguh, Puput Febriany (Seminar Nasional Ilmu Terapan, 2024)
The increasing number of cafés in Surabaya means that there are many job opportunities and currently all places of work are competing to maintain their business, especially in the café sector, this is one of the zones that experiences high turnover. The researcher intends to analyze the work environment and also work involvement by formulating the problem, namely "Does thework environment have an influence on the work commitment of Blue Doors cafe employees in Surabaya?"Then"Does work involvement have an influence on the work commitment of Blue Doors cafe employees in Surabaya?". The aim of this research is to determine whether there is a relationship or influence between the work environment and work involvement, as well as the impact that occurs after improving work environment conditions and dividing employee responsibilities. This research uses quantitative research methods, so that researchers can explore the meaning of visible phenomena and obtain concrete and transparent data. The informants in this research were employees of Bluedoors Surabaya Café, all of whom wereemployees, some of whom worked in the kitchen area, beverage area, cleaning area and financial area. The data obtained from distributing this questionnaire is then processed through the stages of data collection, data testing for validity and reliability, and drawing conclusions. The results of this research show that the work environment has a positive and insignificant effect onorganizational commitment, involvement has a positive and significant effect on organizational commitment, and teamwork has a positive and significant effect on organizational commitment. The results of this research are that the work environment or environmental conditions of the Bluedoors café and the division of tasks are very neatly arranged and take into account theconditions and positions of the employees. The impact felt is that until now Bluedoors has been able to maintain the condition and position of their employees from the start of opening the Surabaya branch until now.